Progress in transparent bulletproof armor based on ceramics - LIU Jia-xi (Journal of Materials Engineering, 2021)
Requirements for the cockpit of military vehicles are constantly increasing as a result of escalating threats. The traditional transparent bulletproof armor based on glass have been unsatisfactory to relevant application requirements, and lighter and thinner transparent armor based on ceramics is becoming main option. Similar to other bulletproof armor, the main research fields of transparent bulletproof armor include:seek materials with higher performance for armor components; guide the structure design and ballistic test by experiment or computer simulation; understand the main performance of armor materials, the holistic performance of the armor system and the interaction between the components of the whole system more deeply. Based on this notion, the advantages and disadvantages, preparation technology, development, and application situation of the three kinds of ceramic materials commonly used in transparent armor were summarized. Among the three kinds of ceramics, sapphire has the best static parameters. As for the actual effect of bulletproof, the polycrystalline ceramics are better. The main reason for this phenomenon is that the different fragmentation modes of the two kinds of ceramics lead to the difference of projectile-target interaction effect. After that, the crack growth under high strain rate and bullet-proof property of single crystal, polycrystalline ceramics and glass were discussed. Under uniaxial, high strain rate compression, the crack propagation characteristics of materials are sensitive to impact energy/velocity. Polycrystalline ceramics has a composite failure mode of intergranular fracture and intragranular fracture. Under high energy impact, the damage zone of sapphire is similar to polycrystalline ceramics. Lower than critical energy, some sapphire plate orientations damage would be dominated. Finally, the material selection standards and structural design principles of each functional layer were summarized and prospected. Fine grain polycrystalline ceramic materials with high Young's modulus and high hardness are preferred for the strike-layer. Materials with good fracture toughness, high bending stiffness and the ability to localization of the damage within a narrow region should be selected for the intermediate layer. The materials of backing layer require ductility and low density. The bulletproof efficiency of the transparent-armor systems depends on the type and the degree of interaction/integration of different functional layers.